SOSIALISASI PENCEGAHAN STUNTING DENGAN PENERAPAN PARENTING YANG BAIK DI PAUD BKB HI KEMAS HARAPAN BUNDA - Ratu Yustika Rini; Novita Sari; Moh Fikri Tanzil; Maulida Nur (LPPM Universitas Bina Bangsa, 2022)
Stunting occurs in vulnerable children aged 0 to 1000 in the first day of life. The period of 1000 days is a period when children are vulnerable to indications of disease, both infectious and non-communicable diseases, as well as an increased risk of being overweight and obese. The graph of the prevalence of stunting under five in the Gunungsari sub-district, Serang Regency in 2018-2021 shows that there are 4 villages whose stunting prevalence has increased, namely Tamiang village rising 1.81%, Sukalaba village increasing 12.95%, Kadu Agung village increasing 5.31%, and Curug Sulanjana rose 22.16%. Parents' perceptions that emphasize the stunting factor are heredity which can cause a passive response or only accept the existing conditions; so that the child is forced to bear all the consequences of stunting for the rest of his life. This problem became the basis for socializing stunting prevention with the application of good parenting in Sukalaba village, Gunungsari sub-district, Serang district. The process of socialization activities goes through several stages, the first is observation, interviews, preparation and socialization. The conclusion of the socialization activity shows that there is hope for participants to carry out good parenting patterns to prevent stunting in children. The responses of stakeholders and participants after participating in this socialization activity varied, 1) The village office was ready to provide healthy meals per 1 month 2 times for children in Sukalaba village, 2) parents felt sad because they had spent precious time with their children, 3) parents feel grateful for being given the opportunity to participate in this outreach activity, 4) parents want to implement stunting prevention efforts for their families, and 5) posyandu cadres are ready to provide assistance for stunting prevention efforts in Sukalaba village. The hope is that awareness of the importance of stunting prevention can run in a sustainable manner.